Long-Read Assembly and Annotation of the Parasitoid Wasp Muscidifurax raptorellus, a Biological Control Agent for Filth Flies - Xiong, Xiao; Kelkar, Yogeshwar D; Geden, Chris J; Zhang, Chao; Wang, Yidong; Jongepier, Evelien; Martinson, Ellen O.; Verhulst, Eveline C; Gadau, Jürgen; Werren, John H; Wang, Xu (Frontiers in Genetics, 2021)
The parasitoid wasp Muscidifurax raptorellus (Hymenoptera: Pteromalidae) is a gregarious species that has received extensive attention for its potential in biological pest control against house fly, stable fly, and other filth flies. It has a high reproductive capacity and can be reared easily. However, genome assembly is not available for M. raptorellus or any other species in this genus. Previously, we assembled a complete circular mitochondrial genome with a length of 24,717 bp. Here, we assembled and annotated a high-quality nuclear genome of M. raptorellus, using a combination of long-read (104× genome coverage) and short-read (326× genome coverage) sequencing technologies. The assembled genome size is 314 Mbp in 226 contigs, with a 97.9% BUSCO completeness score and a contig N50 of 4.67 Mb, suggesting excellent continuity of this assembly. Our assembly builds the foundation for comparative and evolutionary genomic analysis in the genus of Muscidifurax, and possible future biocontrol applications.